2023
DOI: 10.3389/fonc.2023.1169010
|View full text |Cite
|
Sign up to set email alerts
|

Neoadjuvant chemotherapy for breast cancer: an evaluation of its efficacy and research progress

Yushi Chen,
Yu Qi,
Kuansong Wang

Abstract: Neoadjuvant chemotherapy (NAC) for breast cancer is widely used in the clinical setting to improve the chance of surgery, breast conservation and quality of life for patients with advanced breast cancer. A more accurate efficacy evaluation system is important for the decision of surgery timing and chemotherapy regimen implementation. However, current methods, encompassing imaging techniques such as ultrasound and MRI, along with non-imaging approaches like pathological evaluations, often fall short in accurate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 111 publications
0
1
0
Order By: Relevance
“…Studies have con rmed that changes in tumor volume and diameter, as observed through MRI, are among the most accurate indicators of pathological response following treatment. This is especially true for breast cancer NAC, where reducing tumor volume has been identi ed as the most reliable indicator of pathological response, followed closely by changes in tumor diameter [17] .…”
Section: Discussionmentioning
confidence: 99%
“…Studies have con rmed that changes in tumor volume and diameter, as observed through MRI, are among the most accurate indicators of pathological response following treatment. This is especially true for breast cancer NAC, where reducing tumor volume has been identi ed as the most reliable indicator of pathological response, followed closely by changes in tumor diameter [17] .…”
Section: Discussionmentioning
confidence: 99%